Opportunities and Limitations of Hydrogen Energy in Poland against the Background of the European Union Energy Policy - Bednarczyk, Jan L.; Brzozowska-Rup, Katarzyna; Luściński, Sławomir (Energies (Basel), 2022)
One of the strategic goals of developed countries is to significantly increase the share of renewable energy sources in electricity generation. However, the process may be hindered by, e.g., the storage and transport of energy from renewable sources. The European Union countries see the development of the hydrogen economy as an opportunity to overcome this barrier. Therefore, since 2020, the European Union has been implementing a hydrogen strategy that will increase the share of hydrogen in the European energy mix from the current 2 percent to up to 13–14 percent by 2050. In 2021, following the example of other European countries, the Polish government adopted the Polish Hydrogen Strategy until 2030 with an outlook until 2040 (PHS). However, the implementation of the strategy requires significant capital expenditure and infrastructure modernisation, which gives rise to question as to whether Poland is likely to achieve the goals set out in the Polish Hydrogen Strategy and European Green Deal. The subject of the research is an analysis of the sources of financing for the PHS against the background of solutions implemented by the EU countries and a SWOT/TOWS analysis on the hydrogen economy in Poland. The overall result of the SWOT/TOWS analysis shows the advantage of strengths and related opportunities. This allows for a positive assessment of the prospects for the hydrogen economy in Poland. Poland should continue its efforts to take advantage of the external factors (O/S), such as EU support, an increased price competitiveness of hydrogen, and the emergence of a competitive cross-border hydrogen market in Europe. At the same time, the Polish authorities should not forget about the weaknesses and threats that may inhibit the development of the domestic hydrogen market. It is necessary to modernise the infrastructure; increase the share of renewable energy sources in hydrogen production; increase R&D expenditure, and, in particular, to complete the negotiations related to the adoption of the Fit for 55 package.